Forecasting the future of information technology how to make research investment more cost-effective?. - Saracco, R.
This article presents the results of a forecasting project funded by the European Community on the evolution of the technologies and its impact on society in the coming decade. The project requires the development of a methodology to assess the potential impact of technology evolution and provides a tool for decision makers to prioritize the allocation of research investments. A brief outline of some of the technology trajectories identified and possible technology disruptions are given.
Keywords: European Community; Cost-effective investment; Decision making tools; Forecasting project; Information technology; Research investment; Research investments; Technology evolution